Implementasi Monitoring Suhu dan Kelembaban pada Budidaya Jamur Tiram dengan IOT - Yuli Wibowo; Febriansah Eka Prasetyadana; Bertung Suryadharma (The University of Lampung, 2021)
Oyster mushroom commodity has been widely used as raw material for processed food products, monitoring of temperature and humidity intensively, the quality will be well maintained. Monitoring at Rumah Jamur Barokah full 24 hours, so it will be difficult if done manually. This is the reason why it is necessary to design monitoring tools in maintaining the ideal temperature and humidity with the concept of the Internet of Things. This research aims to design temperature and humidity monitoring tools (IoT), and how much the increase value of time efficiency and effectiveness after the tool is implemented. The blackbox testing method is performed for performance feasibility testing, by comparing thermo-hygrometers and sensors. The result of the tool performance test at the temperature parameter obtained an error value 0.33 0C and the DHT22 tolerance limit ± 0.5 0C. In the humidity parameter obtained an error of 1.8% RH and the DHT22 tolerance limit ± 2% RH, so the DHT22 sensor feasible to use. In the analysis of efficiency calculation obtained a result of 77.95% for improved time efficiency. In the analysis of the quality effectiveness value of oyster mushrooms is less than ideal, getting an increase in value by 143% to 163%. Keywords: blackbox testing, cultivation, internet of things (iot), monitoring, oyster mushroom